2023
DOI: 10.3390/min13020206
|View full text |Cite
|
Sign up to set email alerts
|

Silicification of Wood: An Overview

Abstract: For many decades, wood silicification has been viewed as a relatively simple process of permineralization that occurs when silica dissolved in groundwater precipitates to fill vacant spaces within the porous tissue. The presence of specific silica minerals is commonly ascribed to diagenetic changes. The possibility of rapid silicification is inferred from evidence from modern hot springs. Extensive examination of silicified wood from worldwide localities spanning long geologic time suggests that these generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…In the spectrum of kaolin, the absorption peaks at 753 and 789 cm −1 corresponded to the Si–Si stretching vibrations, and the peaks at 1006 and 1114 cm −1 belonged to the Si–O stretching vibrations. 32 In the spectrum of kaolin-modified pigment, the above four peaks disappeared, suggesting kaolin was coated on pigment Red 170, and the characteristic absorption peaks of kaolin were covered.…”
Section: Resultsmentioning
confidence: 99%
“…In the spectrum of kaolin, the absorption peaks at 753 and 789 cm −1 corresponded to the Si–Si stretching vibrations, and the peaks at 1006 and 1114 cm −1 belonged to the Si–O stretching vibrations. 32 In the spectrum of kaolin-modified pigment, the above four peaks disappeared, suggesting kaolin was coated on pigment Red 170, and the characteristic absorption peaks of kaolin were covered.…”
Section: Resultsmentioning
confidence: 99%
“…The correlation is an indicator of the strength of the linear relationship between two variabels, namely 𝑥 and 𝑦 [10], where, 𝑟 is the correlation coefficient, see Equations (1).…”
Section: A Correlationmentioning
confidence: 99%
“…Geological records have shown that wood fossils are majorly found that already naturally silicified. These fossils are millions of years old and are still well-preserved, even on the cellular scale [1][2][3]. It has already replaced carbon-based organic wood fiber with various anorganic oxides, such as silica, manganese, iron, and copper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, X-ray fluorescence spectroscopy maintains its efficacy as an effective method for elemental investigation of wood and subfossil wood (Pereira Junior. et al 2016, Zielenkiewicz et al 2012, Mustoe 2023, Gavrikov et al 2022. Subfossil wood refers to wood that has undergone partial fossilization but has not been yet fully mineralized to become a true fossil.…”
Section: Introductionmentioning
confidence: 99%